2006
DOI: 10.1016/j.regsciurbeco.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Open space, residential property values, and spatial context

Abstract: We use hedonic analysis of home transaction data from the Minneapolis-St. Paul metropolitan area to estimate the effects of proximity to open space on sales price. Importantly, we allow the effects of proximity to vary spatially with many covariates, such as population density and neighborhood income.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
272
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(290 citation statements)
references
References 34 publications
14
272
1
3
Order By: Relevance
“…This segmentation by districts is the first one to be used, each of the equations being The economic literature has focused, by means of capitalization, on the willingness to pay of some neighbourhood amenities such as parks, schools or undergrounds. In this framework, we can emphasize the contributions of Cheshire and Sheppard (1995), Bell and Man (1996), Bilbao-Terol (2000), Bogart and Cromwell (2000), Haider and Miller (2000), Gibbons and Machin (2001), Downes and Zabel (2002) Tse (2002), Anderson and West (2006), Cheshire and Sheppard (2004). However, the main aim of this paper is not to explain variability in housing prices due to the location but to estimate the price and income elasticities of demand for a series of basic housing characteristics (quantity, quality and location), so we decide to replace the amenities variables for the locational dummies.…”
Section: Resultsmentioning
confidence: 99%
“…This segmentation by districts is the first one to be used, each of the equations being The economic literature has focused, by means of capitalization, on the willingness to pay of some neighbourhood amenities such as parks, schools or undergrounds. In this framework, we can emphasize the contributions of Cheshire and Sheppard (1995), Bell and Man (1996), Bilbao-Terol (2000), Bogart and Cromwell (2000), Haider and Miller (2000), Gibbons and Machin (2001), Downes and Zabel (2002) Tse (2002), Anderson and West (2006), Cheshire and Sheppard (2004). However, the main aim of this paper is not to explain variability in housing prices due to the location but to estimate the price and income elasticities of demand for a series of basic housing characteristics (quantity, quality and location), so we decide to replace the amenities variables for the locational dummies.…”
Section: Resultsmentioning
confidence: 99%
“…Walsh et al (2011) [9] identified the significance of water body proximity on the value of residential properties in Orange County, Florida. Positive amenities from proximity to water are also reported by Anderson and West (2006) [10]. Tapsuwan et al (2009) [11] argue that the value of houses increases by reducing the distance to the wetland.…”
Section: Introductionmentioning
confidence: 93%
“…In certain cases, time-invariant variables are omitted in the empirical model because these may not be observed due to the limited data available. However, time-invariant variables measured at the same scale of the fixed effects variables are controlled [55][56][57]. Thus, the fixed effects regression model can specify how changes in time-varying control variables account for the change in the proportion and number of walking trips over time because time-invariant unobserved variables that are fixed over time have been "differenced away" in the analysis [54].…”
Section: Model Specificationmentioning
confidence: 99%